A MODEL TO ENSURE QUALITY MANAGEMENT OF SCIENCE AND TECHNOLOGY FOR AUTONOMOUS INSTITUTIONS IN VIETNAM : Received: 27th December 2024 Revised: 12th February 2024, 28th February 2024 & 3rd March 2024 Accepted: 3rd January 2024 - Le Thi Thuong, (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Alongside internal quality assurance measures, external quality assessment serves as a mechanism to ensure the quality of education in Vietnam, proven to offer various opportunities (enrollment, research collaboration, technology transfer, etc.) as relevant parties become aware of and trust in the educational institution's quality. Consequently, the impact of educational quality assessment prompts systematic quality assurance activities within the university, yielding high results based on post-assessment expert recommendations. However, among the university activities in Vietnam, scientific and technological management has been identified as one of the few standards with a relatively low average score (Hien et al., 2022); Anh, 2022). Proposing a suitable research model to assess the influence of educational quality assessment on the scientific and technological management of autonomous universities in Vietnam will assist these institutions in identifying crucial elements of scientific and technological management. This will facilitate the implementation of more feasible activities to ensure the quality of these operations, contributing significantly to the overall educational quality of the institution.